The role of microorganisms in mineral transformation, characterized by spectroscopic methods: a review (Research, Society and Development, 2022)
The microbial biomass has great responsibility in the biogeochemical transformations in the soil, being the most responsible for the mineralization, immobilization and availability of nutrients to the plants, some mass spectrometry techniques are being widely used, in order to know how these transformations happen in the biomass of the soil, in addition to identifying the variation and distribution of microorganisms present in the medium. Due to the complexity of organisms that may be present in the microbiota, it is interesting to use fast and practical methods. In this sense, the objective of this review was to better understand the use of new techniques that are being employed and improved in the sampling and resolution of these activities, as well as to demonstrate their effectiveness both for sampling nutrition and the recognition of organisms present in the soil, pointing out new research opportunities. Understanding that, because this is a very simple method that presents good results, it is possible to use some methods in academic research, and may become a decisive tool in the search for more satisfactory results and with greater precision.